Dissensuous Modernism : Women Writers, the Senses, and Technology - DeMaagd, Allyson C. (Book collections on Project MUSE., 2022)
Placing women writers at the centre of the sensory and technological experimentation that characterized the modernist movement, 'Dissensuous Modernism' shows how women of the era challenged gendered narratives that limited their power and agency and waged dissent through their radical sensuous writing.